2018
DOI: 10.1186/s12913-018-3421-2
|View full text |Cite
|
Sign up to set email alerts
|

A pre and post intervention study to reduce unnecessary urinary catheter use on general internal medicine wards of a large academic health science center

Abstract: BackgroundUrinary catheters are a common medical intervention, yet they can also be associated with harmful adverse events such as infection, urinary tract trauma, delirium and patient discomfort. The purpose of this study was to describe the use of the SafetyLEAP program to drive improvement efforts, and specifically to reduce the use of urinary catheters on general internal medicine wards.MethodsA pre and post intervention study using the SafetyLEAP program was performed with urinary catheter prevalence as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
1
14
1
Order By: Relevance
“…Of the included papers, 61 focussed on clinical audits, 17 on accreditation/certification and 7 on peer reviews. In terms of the evidence levels established by EPOC review group [ 30 ], one randomised trial was found [ 35 ], two controlled studies [ 36 , 37 ], 66 case studies [ 38 103 ], and 16 descriptive studies [ 104 119 ]. Using the QI-MQCS, the completeness of reporting scores ranged from 4 to 16 (16 being the highest possible score) ( S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the included papers, 61 focussed on clinical audits, 17 on accreditation/certification and 7 on peer reviews. In terms of the evidence levels established by EPOC review group [ 30 ], one randomised trial was found [ 35 ], two controlled studies [ 36 , 37 ], 66 case studies [ 38 103 ], and 16 descriptive studies [ 104 119 ]. Using the QI-MQCS, the completeness of reporting scores ranged from 4 to 16 (16 being the highest possible score) ( S1 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Having a sense of urgency seems to be an important precondition for healthcare professionals to engage: if healthcare professionals perceive the current situation as untenable for themselves or for the safety of patients, this will urge them to take action [ 82 , 105 ]. Several studies have described local audits that were started by intrinsically motivated healthcare professionals on issues they felt to impact on patient care [ 48 , 53 , 61 , 63 , 69 , 82 , 88 , 97 , 99 , 103 ]. In contrast, if healthcare professionals perceive an audit as a ‘side-line’ or ‘mandatory exercise’, rather than a process to contribute to improved quality of care, they will not feel engaged and not put significant effort into the change [ 77 , 118 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, it provides rich details about the events allowing for timely identification and assessment of cases which can be used to prioritise opportunities for improvement. 33 34…”
Section: Introductionmentioning
confidence: 99%
“…Previous pilot work on the general internal medicine units at a large academic health science centre showed a decrease in the incidence of catheter use from approximately 25% of patients down to 12-15% after implementation of a standardized protocol [15]. This was also associated with decreased antibiotic prescribing for catheter-associated bacteriuria on these units, which was sustained for over a year [15].…”
Section: Protocolmentioning
confidence: 97%